Vitamin D Status and SARS-CoV-2 Infection and COVID-19 Clinical Outcomes - Chiodini, Iacopo; Gatti, Davide; Soranna, Davide; Merlotti, Daniela; Mingiano, Christian; Fassio, Angelo; Adami, Giovanni; Falchetti, Alberto; Eller-Vainicher, Cristina; Rossini, Maurizio; Persani, Luca; Zambon, Antonella; et al. (Frontiers in Public Health, 2021)
Background. Several studies suggest an association between serum 25-hydroxyvitamin D (25OHD) and the outcomes of Severe Acute Respiratory Syndrome Corona-Virus-2 (SARS-CoV-2) infection, in particular Coronavirus Disease-2019 (COVID-19) related severity and mortality. The aim of the present meta-analysis was to investigate whether vitamin D status is associated with the COVID-19 severity, defined as ARDS requiring admission to intensive care unit (ICU) or mortality (primary endpoints) and with the susceptibility to SARS-CoV-2 and COVID-19-related hospitalization (secondary endpoints). Methods. A search in PubMed, ScienceDirect, Web of Science, Google Scholar , Scopus and preprints repositories was performed until March 31th 2021 to identify all original observational studies reporting association measures, or enough data to calculate them, between Vitamin D status (insufficiency <75, deficiency <50 or severe deficiency <25 nmol/L) and risk of SARS-CoV-2 infection , COVID-19 hospitalization, ICU admission or death during COVID-19 hospitalization. Findings: 54 studies (49 as fully-printed and 5 as pre-print publications) were included for a total of 1 403 715 individuals. The association between vitamin D status and SARS-CoV2 infection, COVID-19 related hospitalization, COVID-19 related ICU admission and COVID-19 related mortality was reported in 17, 9, 27 and 35 studies, respectively. Severe deficiency, deficiency and insufficiency of vitamin D were all associated with ICU admission (odds ratio [OR], 95% confidence intervals [95%CIs]: 2·63, 1·45-4·77; 2·16, 1.43-3.26; 2.83, 1·74-4·61, respectively), mortality (OR, 95%CIs: 2·60, 1·93-3·49; 1·84, 1·26-2·69; 4·15, 1·76-9·77, respectively), SARS-CoV-2 infection (OR, 95%CIs: 1·68, 1·32-2·13; 1·83, 1·43-2·33; 1·49, 1·16-1·91, respectively) and COVID-19 hospitalization (OR, 95%CIs 2·51, 1·63-3·85; 2·38, 1·56-3·63; 1·82, 1·43-2·33). Considering specific subgroups (i.e. Caucasian patients, high quality studies and studies reporting adjusted association estimates) the results of primary endpoints did not change. Interpretations. Patients with low vitamin D levels present an increased risk of ARDS requiring admission to intensive care unit (ICU) or mortality due to SARS-CoV-2 infection and a higher susceptibility to SARS-CoV-2 infection and related hospitalization